Technological advances in cardiac pacing and defibrillation - Sok-Sithikun Bun; Fabien Squara; Didier Scarlatti; Guillaume Theodore; Decebal Gabriel Latcu; Karim Hasni; Fatima Azzahrae Benaich; Emna Allouche; Nadir Saoudi; Emile Ferrari (Heart Vessels and Transplantation, 2019)
Since more than a half century, cardiac pacing and defibrillation represent a field in constant evolution, and they have shown some great technological advances from its conception to its methods of insertion.